AHP Techniques for Persian Text Summarization - Tofighy, Seyyed Mohsen; Raj, Ram Gopal; Seyyed Javad, Hamid Haj (Malaysian Journal of Computer Science, 2013)
In recent years, there has been an increasing amount of information on the web. Some of essential resources to shorten text documents use summarization technologies. In this paper, we present an AHP technique for Persian Text Summarization. This proposed model uses analytical hierarchy as a base factor for an evaluation algorithm and improves the summarization quality of Persian language text. The weighting and combination methods are two main contributions of the proposed text evaluation algorithm.